Prevalence and prognostic impact of retropharyngeal lymph nodes metastases in oropharyngeal squamous cell carcinoma: Meta‐analysis of published literature. Issue 10 (1st August 2022) - Tirelli, Giancarlo; Gardenal, Nicoletta; Zanelli, Enrico; Borsetto, Daniele; Phillips, Veronica; Marcuzzo, Alberto Vito; Fussey, Jonathan; Polesel, Jerry; Boscolo‐Rizzo, Paolo
Abstract: Background: This systematic review and meta‐analysis aims to estimate the prevalence and prognostic impact of retropharyngeal lymph node metastases (RLNMs) in oropharyngeal squamous cell carcinoma (OPSCC). Methods: This meta‐analysis was conducted according to PRISMA guidelines. Inclusion criteria: studies with more than 20 patients reporting the prevalence or prognostic impact of RLNMs in OPSCC. Whenever available, data on HPV status and subsites were extracted. Results: Twenty‐two articles were included. The overall prevalence of RLNMs in OPSCC was 13%, with no significant differences depending on HPV status. The highest prevalence was observed for posterior pharyngeal wall SCC (24%), followed by soft palate (17%), palatine tonsil (15%), and base of tongue (8%). RLNMs were associated with a significantly higher risk of death (HR:2.54;IC95%1.89–3.41) and progression (HR:2.44;IC95%1.80–3.30). Conclusions: The prevalence of RLNMs in OPSCC was 13%, being higher in tumors of the posterior pharyngeal wall. RLNMs were associated with unfavorable outcomes.